Epilepsy surgery in early infancy: A retrospective, multicenter study - Konstantin L. Makridis; Kerstin Alexandra Klotz; Georgia Ramantani; Lena‐Luise Becker; Victoria San Antonio‐Arce; Steffen Syrbe; Kathrin Wagner; Mukesch Johannes Shah; Ulrich‐Wilhelm Thomale; Anna Tietze; Christian E. Elger; Ingo Borggraefe; et al. (Epilepsia Open, 2023)
Abstract Although epilepsy surgery is the only curative therapeutic approach for lesional drug‐resistant epilepsy (DRE), there is reluctance to operate on infants due to a fear of complications. A recent meta‐analysis showed that epilepsy surgery in the first 6 months of life can achieve seizure control in about two thirds of children. However, robust data on surgical complications and postoperative cognitive development are lacking. We performed a retrospective multicenter study of infants who underwent epilepsy surgery in the first 6 months of life. 15 infants underwent epilepsy surgery at a median age of 134 days (IQR: 58) at four centers. The most common cause was malformation of cortical development, and 13 patients underwent a hemispherotomy. Two thirds required intraoperative red blood transfusions. Severe intraoperative complications occurred in two patients including death in one infant due to cardiovascular insufficiency. At a median follow‐up of 1.5 years (IQR: 1.8), 57% of patients were seizure‐free. Three patients where reoperated at a later age, resulting in 79% seizure freedom. Anti‐seizure medication could be reduced in two thirds, and all patients improved in their development. Our findings suggest that early epilepsy surgery can result in good seizure control and developmental improvement. However, given the perioperative risks, it should be performed only in specialized centers.